BUNGA BANK: ANTARA PARADIGMA TEKSTUAL DAN KONTEKSTUAL - Hasyim, Muhammad Syarif (State Institute of Islamic Studies (IAIN) Palu, 2008)
Bank interest is an interesting topic to discuss from classical era to modern era. In classical era, interest has been decided as ribâ., the law status of which is harâm (forbidden) because of an addition (ziyâdah). Based on this, bank interest is also categorized as ribâ. Nevertheless, some say that the forbiddance of ribâ is because of an exploitation to the clients, based on which bank interest is not ribâ. It is based on these two opinions that a controversy on bank interest emerges. The controversy emerges since the first group interprets the verses on ribâ textually while the second group interprets the verses contextually.Kata Kunci: bunga bank, paradigma tekstual, paradigma kontekstual